CHROMIUM PHYTOACCUMULATION BY ALTERNANTHERA SESSILIS IN VITRO – A FIRST REPORT - SUBHALAKSHMI A,; RAJAGOPAL K,; NITHIYANANDHAN G,; JAYANANDI DEVI,; KARTHIKEYAN S, (International Journal of Pharma and Bio Sciences, 2013)
The present study established a protocol for assessing in vitro chromium absorption potential of Alternanthera sessilis. The study also investigated the effect of chromium on morphology of the micropropagated plants. Murashige and Skoog (1962) medium fortified with 0.5 mg/l of 6-benzylaminopurine (BAP) and 0.2 mg/l Indole-3 acetic acid (IAA) was selected as ‘in vitro plantlet induction medium (IVPI)’ for A. sessilis. Optimum chromium uptake (OCU) concentration was determined as 8 mg/l K2Cr2O7 on which moderate effects in length of shoot (4.5 cm) and root (1.2 cm) and survival rate (58.6%) was recorded. The chromium accumulation of A. sessilis at OCU concentration is comparatively similar in both in vitro condition (1011 μg/g in root; 201 μg/g in shoot) and Hydroponics (996 μg/g in root; 195 μg/g in shoot). The in vitro method was found to be a valuable tool in identifying prospective phytoremediation candidates to reduce environmental toxic metals.